2017
DOI: 10.1016/j.bbi.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The placental interleukin-6 signaling controls fetal brain development and behavior

Abstract: Epidemiological studies show that maternal immune activation (MIA) during pregnancy is a risk factor for autism. However, mechanisms for how MIA affects brain development and behaviors in offspring remain poorly described. To determine whether placental interleukin-6 (IL-6) signaling is required for mediating MIA on the offspring, we generated mice with restricted deletion of the receptor for IL-6 (IL-6Rα) in placental trophoblasts (Cyp19-Cre+;Il6rafl/fl), and tested offspring of Cyp19-Cre+;Il6rafl/fl mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
170
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(191 citation statements)
references
References 70 publications
7
170
1
Order By: Relevance
“…While transplacental fetal infection does occur, there was no significant effect of positive viral infection on any analyses in our model. Epidemiological studies assessing the risks from maternal infection for psychiatric disorders in offspring indicate that both pathogens which are transmissible to the fetus (rubella virus, cytomegalovirus, herpes simplex virus, and Toxoplasma gondii ) and those that are nontransmissible (influenza virus) confer a risk [2, 66]; animal models strongly suggest that the maternal inflammatory response (i.e., cytokines such as IL-6 and IL-17a), and not the pathogen, drives the detrimental effects of MIA on the neurodevelopment and behavior of the offspring [13, 14, 19]. Thus, in our model, PRRSV infection serves to activate a maternal immune response comparable to that observed during human viral infections, such as influenza.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While transplacental fetal infection does occur, there was no significant effect of positive viral infection on any analyses in our model. Epidemiological studies assessing the risks from maternal infection for psychiatric disorders in offspring indicate that both pathogens which are transmissible to the fetus (rubella virus, cytomegalovirus, herpes simplex virus, and Toxoplasma gondii ) and those that are nontransmissible (influenza virus) confer a risk [2, 66]; animal models strongly suggest that the maternal inflammatory response (i.e., cytokines such as IL-6 and IL-17a), and not the pathogen, drives the detrimental effects of MIA on the neurodevelopment and behavior of the offspring [13, 14, 19]. Thus, in our model, PRRSV infection serves to activate a maternal immune response comparable to that observed during human viral infections, such as influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Wu et al [14] and Mouihate and Mehdawi [15] demonstrated an increased expression of IL-6, STAT3, and pSTAT3 in the fetal brain in the immediate hours following MIA, though these studies did not extend past 24 h after MIA induction. In fact, the most compelling and comprehensive evidence of the impact of MIA on fetal brain gene and protein expression to date has focused on the immediate time points following immune activation [19, 90], and several studies support the idea that neuroinflammation is resolved by the neonatal and postnatal periods [79, 81, 91].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BPH/5, a mouse model with mild hypertension, revealed abnormal placentation, FGR, excessive C3 deposition and neutrophil infiltration in the ectoplacental cone at E6.5 and E8.5 respectively, consistent with reduced levels of VEGF in the placenta and enhanced levels of TNF-α released by neutrophils (Gelber et al 2015). In addition, activation of mouse maternal innate immune system by intravenous administration of polyinosinic-polycytidylic acid (poly(I:C)), a nonpathogenic antigen, caused cerebellar neuropathology and behavioral abnormalities in the offspring, which were mediated by an increased IL-6 signaling in the placenta (Wu et al 2017).…”
Section: R230mentioning
confidence: 99%